Virtual Try On Sebagai Determinan terhadap Keputusan Pembelian Dimoderasi oleh Ulasan Pelanggan - Hary Firmansyah; Nurna Yuni; Depy Muhamad Pauzy (Universitas Muhammadiyah Bengkulu, 2026)
Virtual Try-On (VTO) technology in e-commerce is used to reduce uncertainty when purchasing experiential products such as skincare, which serve various functions and target diverse consumer segments. A novel aspect of this research was the examination of the usefulness of Virtual Try-On. The purpose of this study was to investigate the effect of VTO usage on purchasing decisions. It also analyzed the moderating role of customer reviews in the relationship between VTO use and purchasing decisions. The method employed was quantitative explanatory research. The results revealed that all indicators for each variable were valid and reliable. The use of the VTO feature had a significant effect on purchasing decisions, both partially and simultaneously. Customer reviews did not have a moderating or significant influence on the effect of VTO on purchasing decisions. Virtual Try-On was identified as a primary determinant of online purchasing decisions for skincare products. The success of VTO depends on its functional aspects and the enjoyable experience it provides. The effectiveness of VTO increases when supported by positive customer reviews. Integrating VTO technology strategies with online product differentiation through customer reviews is important for increasing sales conversions.